Adverse Event Following Immunization and Relation with Blood Group Following COVID19 Vaccination among Indian Community: A Cross-Sectional Study - Niraj Pandit; Nilesh Patel (Journal of Integrated Health Sciences)
Introduction: In middle of the 3rd wave, COVID19 is now gradually making agent host environment balance at the world level. COVID19 vaccine is also available for the prevention of diseases. The two vaccines which are available in India till July 2021, they are COVISHIELD and Covaxin. There are various news heard about the relation of the ABO blood group and COVID19 disease. However, no study has tried to the relation of various blood groups and adverse events following immunization (AEFI). Methods: This was a community-based cross-sectional study. It was conducted online mode with the use of Google Forms. Study participants were Indian citizens and who took either Covishield or Covaxin as COVID19 vaccination. The pretested form was used, which consisted of various information regarding blood group of individual, vaccine, type of vaccine, doses of vaccine, side effects postvaccination, what is/are side effects and other information like do you have disease COVID19. Results: A total of 893 participated in the study, but out of them, 731 participants took vaccine either one or two doses. Most of the participants, 597 (87%), were from urban areas. The postCOVID19 vaccine AEFI prevalence was 69.7%. The association between ABO and Rh blood group and AEFI was not statistically significant. However, Covaxin has lesser side effects compared to COVISHIELD. Even a small group of COVID19 disease also had no association with ABO or Rh blood group. Conclusion: The side effects following the COVID19 vaccine are quite common. Majority were mild AEFI. There is no statistical association with blood group and postCOVID19 AEFI.